A modified Lichtenstein technique in the management of female groin hernia: A pilot study - Axel Eriksson; Fredrik Lindmark; Kristina Borenberg; Pär Nordin (International Journal of Abdominal Wall and Hernia Surgery)
AIM: Femoral hernia is associated with a higher complication risk compared to inguinal hernia. Most groin hernia research studies today are performed on men. The Lichtenstein technique is a well-studied, safe, and widely used method in men, but not recommended in women, where the recommended approach is either endoscopic or an open preperitoneal technique. MATERIALS AND METHODS: A case–control pilot study was performed on adult women with groin hernia repaired using a modified Lichtenstein (ML) technique. The technique is the same as the original Lichtenstein method, with the addition of an incision in the posterior wall of the inguinal canal. If a femoral hernia or weakening is found, a mesh flap is applied to cover the femoral orifice. The primary outcome was perioperative complications, and the secondary outcome was long-term complications. RESULTS: In this pilot study, 48 women were operated with the ML technique. Only minor perioperative complications were seen, and no serious adverse events occurred. The complications were transient, and no unplanned hospital admission was necessary. No recurrent hernias occurred during the follow-up period, only a few women were dissatisfied with the procedure, and even less reported persisting pain. CONCLUSION: This ML technique could be an alternative method for female groin hernia repair. This pilot study paves the way for further research and development of this method, which eventually could be used in resource-limited settings or where the surgeon is not specialized in hernia repair.